Nutrients concentrations measured on water bottle samples during Akademik Tryoshnikov cruise Arctic Century 2021 Expedition (AT21), Arctic Ocean - Sofia Muller; François Fripiat; Mareike Schmitt; Samuel L Jaccard; Jens A Hölemann; Bruno Delille; Mikhail Makhotin; Heidemarie Kassens; Alfredo Martínez-García (PANGAEA, 2024)
Sea water samples were collected as part of the Arctic Century Expedition, which took place in the Kara Sea (Arctic Ocean) aboard the research vessel Akademik Tryoshnikov between August and September 2021. A total of 52 stations (633 samples) were sampled for full-depth profile measurements of dissolved inorganic nutrients concentrations (nitrate, nitrite, phosphate, silicate). This dataset is related to the Gangnus et al. (2022) dataset (doi:10.1594/PANGAEA.947808), with the difference that measurements were performed on frozen samples at home laboratory using a standard colorimetric method following Hydes et al. (2010), (doi:10.25607/OBP-15). The dataset is particularly relevant for nitrogen isotope studies, as the measurements were performed on the same water bottles. Temperature and salinity data from water bottle samples were provided by the Gangnus et al. (2022) dataset (doi:10.1594/PANGAEA.947808). The data are provided by the Arctic Century Expedition, a joint initiative led by the Swiss Polar Institute (SPI), the Antarctic and Arctic Research Institute (AARI) and GEOMAR Helmholtz Centre for Ocean Research Kiel (GEOMAR) and funded by the Swiss Polar Foundation, AARI, Minobrnauki (CATS RFMEFI61619X0108) and BMBF (CATS 03F0831).